Dietary Fish Oil Concentrates Associated Health Benefits: A Recent Development of Cardiovascular Risk Reduction - Behera, Sudhanshu S. (Current Pharmaceutical Design, 2019)
Fish oil is an abundant source of omega-3 (n-3 or ω-3) polyunsaturated fatty acids (PUFAs) and contains Eicosapentaenoic Acid (EPA) and Docosahexaenoic Acid (DHA). PUFAs are very effective in preventing/ inhibiting cardiovascular incidents, particularly in individuals with high cardiovascular risk/accidents. In this review, composition, extraction of fish oil and its favorable/beneficial effects in Cardiovascular Diseases (CVDs) and molecular mechanism for its treatment/reduction have been discussed. Moreover, the application of fish oil for preventive/protective and remedial/curative properties in nutritive and health benefits has been summarized. All these aspects further search the opportunities/hope and scope with its expected opening and anticipations/ possibilities to provide additional therapeutic substitutes for the reduction of CVDs and registration of new drugs.
Keywords: molecular mechanism